2017
DOI: 10.3727/105221616x693855
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib and 2-Deoxyglucose Synergistically Inhibit Proliferation of Both Sorafenib-Sensitive and -Resistant HCC Cells by Inhibiting ATP Production

Abstract: Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths globally1,2. Sorafenib is the only first-line systemic drug for advanced HCC, but it has very limited survival benefits because patients treated with sorafenib either suffer from side effects or show disease progression after initial response. Thus, there is an urgent need to develop novel strategies for first-line and second-line therapy. The association between sorafenib resistance and glycolysis prompted us to screen severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…Fiume et al found that Sora treatment could damage OXPHOS and promote aerobic glycolysis in cells grown in a glucose rich environment [45]. Reyes et al found that Sora and 2-Deoxyglucose (2-DG) co-treatment could synergistically inhibit the proliferation of Sora resistant HCC cells by inhibiting ATP production [34]. It was also shown by Wong et al that 2-DG can reverse Sora resistance in HCC [44].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Fiume et al found that Sora treatment could damage OXPHOS and promote aerobic glycolysis in cells grown in a glucose rich environment [45]. Reyes et al found that Sora and 2-Deoxyglucose (2-DG) co-treatment could synergistically inhibit the proliferation of Sora resistant HCC cells by inhibiting ATP production [34]. It was also shown by Wong et al that 2-DG can reverse Sora resistance in HCC [44].…”
Section: Discussionmentioning
confidence: 97%
“…The mechanisms of Sora resistance remain obscure, but new insights include a higher EGFR, c-Jun and Akt activation in HCC cells, as well as increased EMT, cancer stem cells, hypoxic environment, autophagy, and exosomes [2,5,34,41,42]. Recently, several studies reported that aerobic glycolysis may also contribute to Sora resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic processes are demonstrated to exhibit consistent prognostic patterns, and they are associated with the sensitivity of drugs in clinical use. 2-deoxy-D-glucose, a common glycolytic inhibitor, could drastically inhibit the growth of sorafenib-resistant cells [41]. Glucose uptake and lactate export have also been enhanced in response to sorafenib [42].…”
Section: Metabolic Switch Of Glucose Metabolism and Alternative Energmentioning
confidence: 99%
“…On the other hand, elaboration of sorafenib was targeted to add molecules which could acts as biological enhancers in a synergistic way. Two examples of molecules used with this intent are C2-ceramide[ 97 ], a potent inducer of apoptosis in human neoplastic cells, and 2-Deoxyglucose[ 98 ], an inhibitor of glycolysis that leads to depletion of ATP.…”
Section: Future Perspectivesmentioning
confidence: 99%